2005
DOI: 10.1002/mnfr.200500068
|View full text |Cite
|
Sign up to set email alerts
|

Influence of food acidulants on bioaccessibility of zinc and iron from selected food grains

Abstract: Four common acidulants in Indian dietary, i. e., citric acid, tamarind (Tamarindus indica), amchur (Mangifera indica), and kokum (Garcinia indica) were examined for a possible influence on the bioaccessibility of zinc from selected food grains. Among the four acidulants examined, amchur and citric acid generally enhanced the bioaccessibility of zinc and iron from all the food grains studied. The increase in zinc bioaccessibility produced by citric acid was around 40% in rice and chickpea, while amchur produced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 8 publications
(7 reference statements)
2
32
0
Order By: Relevance
“…The much practiced heat processing, germination, and fermentation of grains, as encountered during China culinary practices, have beneficial influences on mineral bioaccessibility. Similarly, the beneficial influence of food acidulants commonly used in China on mineral availability has also been documented (Hemalatha, Platel, & Srinivasan, 2005). This study is the first report on the beneficial influence of germination, a traditional process that is employed at both domestic and commercial levels, especially in the manufacture of weaning and geriatric foods, on mineral availability.…”
Section: Resultsmentioning
confidence: 68%
“…The much practiced heat processing, germination, and fermentation of grains, as encountered during China culinary practices, have beneficial influences on mineral bioaccessibility. Similarly, the beneficial influence of food acidulants commonly used in China on mineral availability has also been documented (Hemalatha, Platel, & Srinivasan, 2005). This study is the first report on the beneficial influence of germination, a traditional process that is employed at both domestic and commercial levels, especially in the manufacture of weaning and geriatric foods, on mineral availability.…”
Section: Resultsmentioning
confidence: 68%
“…Organic acids are known enhancers of mineral bioaccessibility (Hemalatha, Platel, & Srinivasan, 2005). Thus, to examine the effect of citric acid on iron bioaccessibility from fortified millet flour, citric acid was added along with ferrous fumarate and EDTA; as well as ferrous fumarate and folic acid at a level of 500 mg/100 g flour.…”
Section: Effect Of Citric Acid Co-fortified Along With Iron On the Bimentioning
confidence: 99%
“…Ascorbic acid and other organic acids are well known promoters of iron absorption from the diet (Hallberg, Brune, & Rossander, 1986;Hemalatha, Platel, & Srinivasan, 2005). It has been reported that vitamin A and b-carotene can enhance non-heme iron absorption and thereby contribute to an increase in haemoglobin levels (Gracia-Casal et al, 1998).…”
Section: Introductionmentioning
confidence: 99%